2006
DOI: 10.1002/pbc.21031
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of the RASSF1A gene predicts the poor outcome of patients with hepatoblastoma

Abstract: RASSF1A methylation may be a novel molecular-genetic marker for treatment outcome in hepatoblastoma if confirmed by studies examining a larger number of hepatoblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…The present and previous studies evaluated the methylation status of at least 20 genes in hepatoblastoma and found that only 3 genes were methylated (Table IV). 9,34,35 The limited number of methylated genes suggest that this profile may be specific for hepatoblastoma, 38 and the survival and stage distribution analyses disclosed that combined RASSF1A and SOCS1 or CASP8 methylation, or joint methylation of the 3 genes are not correlated with the advanced stage of disease or a poor outcome, contrary to the findings that methylation of multiple genes were correlated with a poor outcome, reported in neuroblastoma. 39 The present multivariate analysis identified unresectable tumor stages of disease (3B and 4) as the most significant factor predicting overall survival, followed by RASSF1A methylation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The present and previous studies evaluated the methylation status of at least 20 genes in hepatoblastoma and found that only 3 genes were methylated (Table IV). 9,34,35 The limited number of methylated genes suggest that this profile may be specific for hepatoblastoma, 38 and the survival and stage distribution analyses disclosed that combined RASSF1A and SOCS1 or CASP8 methylation, or joint methylation of the 3 genes are not correlated with the advanced stage of disease or a poor outcome, contrary to the findings that methylation of multiple genes were correlated with a poor outcome, reported in neuroblastoma. 39 The present multivariate analysis identified unresectable tumor stages of disease (3B and 4) as the most significant factor predicting overall survival, followed by RASSF1A methylation.…”
Section: Discussionmentioning
confidence: 91%
“…31 Previous studies, including ours, have repeatedly shown that promoter hypermethylation of RASSF1A correlated with loss of expression in various cancers, and treatment with a demethylating agent reactivated RASSF1A gene expression in various cancer cell lines, including a hepatoblastoma cell line HepG2. 9,34,36,37 RASSF1A inhibits tumor formation by apoptosis, and regulates microtubule dynamics and mitotic arrest via multiple effectors. By dysregulation of the Ras signaling pathway, RASSF1A methylation is correlated with poor differentiation and vascular invasion of cancer cells, and an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the mortality of these patients, innovative treatment based on a specific molecular target is needed. The molecular mechanism involved in the development and progression of HB includes overexpression of insulin-like growth factor-II (IGF2) (Li et al, 1998b;Gray et al, 2000;Hartmann et al, 2000), downregulation of RASSF1A by promoter hypermethylation (Sugawara et al, 2007;Honda et al, 2008) and alterations of genes in the Wnt signalling pathway; most notably, the high incidence of CTNNB1 (catenin, b1) mutation (Koch et al, 1999;Taniguchi et al, 2002).…”
mentioning
confidence: 99%